The Effectiveness of the Inquiry Learning Model on Basic Science Learning Materials on Problem Solving and Critical Thinking Skills - Ni Made Pujani (Jurnal Pendidikan dan Pengajaran, 2022)
Science has an important role because students can get to know the surrounding environment and all its contents. Therefore science learning needs to be presented with a good and relevant learning model that can support the development of science and technology. One suitable learning model is inquiry-based science learning, it can provide problem-based learning that can train students to solve problems. This research study was aimed to improve problem-solving and critical thinking skills for science prospective teachers. The study was carried out by implementing a Basic Science learning tools based on an inquiry model for the first semester students of the Department of Science Education Universitas Pendidikan Ganesha. The research employed a one-group pretest-posttest design. The results of the study showed that the inquiry learning model is effective for improving the quality of problem-solving skills and effective for improving the quality of critical thinking skills for science prospective teachers.